2022
DOI: 10.1016/j.jbc.2021.101518
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the SARS-CoV-2 NSP14 3′–5′ exoribonuclease by NSP10 and response to antiviral inhibitors

Abstract: Understanding the core replication complex of SARS-CoV-2 is essential to the development of novel coronavirus-specific antiviral therapeutics. Among the proteins required for faithful replication of the SARS-CoV-2 genome are NSP14, a bifunctional enzyme with an N-terminal 3'-to-5' exoribonuclease (ExoN) and a C-terminal N7-methyltransferase (N7-MTase), and its accessory protein, NSP10. The difficulty in producing pure, high quantities of the NSP10/14 complex has hampered the biochemical and structural study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…Alongside N7-methyltransferase activity, nsp14 harbors an ExoN domain characterized by exoribonuclease activity; an activity essential for proofreading during virus replication. However, in vitro , nsp14 is characterized by the high processivity and non-specifically degrades nucleic acids 17,24,25 . As the nuclease activity must be tightly controlled, we assessed whether the complex formation regulates this process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alongside N7-methyltransferase activity, nsp14 harbors an ExoN domain characterized by exoribonuclease activity; an activity essential for proofreading during virus replication. However, in vitro , nsp14 is characterized by the high processivity and non-specifically degrades nucleic acids 17,24,25 . As the nuclease activity must be tightly controlled, we assessed whether the complex formation regulates this process.…”
Section: Resultsmentioning
confidence: 99%
“…Nsp14 also harbours exoribonuclease activity, essential for proofreading during virus replication. However, in vitro, the protein acts as a highly processive ribonuclease, unspecifically degrading nucleic acids 19 . As the nuclease activity must be tightly controlled, we assessed whether the complex formation regulates this process.…”
Section: Functional Consequences Of Nsp10/14/16 Complex Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of Nsp10, Nsp14 exonuclease activity is negligible; however, the mechanism of stimulation is still unknown. Possible explanations include structural support or increased RNA‐binding contacts [ 35 ]. Cryo‐Electron Microscopy (EM) structures of the core RTC with multiple accessory factors revealed that the ExoN domain also makes contacts with additional RTC members including Nsp12, Nsp8, and Nsp9 (Fig.…”
Section: Nsp14mentioning
confidence: 99%
“…24,25 It uses the original viral positive-sense RNA strand to produce an intermediate negative-sense strand which is further used as a template allowing the synthesis of a novel duplicated positive-sense RNA strand. Of note, the RNA replication takes place in the cytoplasm in double-membrane vesicles and differently from other RNA viruses, SARS-CoV-2 also disposes of a replication proof-reading system based on a viral exonuclease, 26,27 which limits replication errors and considerably slows down its mutation rate. Obviously SARS-CoV-2 RNAP constitutes an ideal target for possible pharmacological development., [28][29][30] Its inhibition would, indeed, result in the arrest of the viral replication cycle and of the infection.…”
Section: Introductionmentioning
confidence: 99%